Nonlinear Fuzzy Differential Equation with Time Delay and Optimal Control Problem - Wichai Witayakiattilerd (Abstract and Applied Analysis)
The existence and uniqueness of a mild solution to nonlinear fuzzy differential equation constrained by initial value were proven. Initial value constraint was then replaced by delay function constraint and the existence of a solution to this type of problem was also proven. Furthermore, the existence of a solution to optimal control problem of the latter type of equation was proven.